DETERMINANTS OF DEMAND FOR GOVERNMENT AGRICULTURAL LOANS USING THE LOGIT MODEL - Noor. M. H; A. F. Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The research aims to enhance farmers’ access to agricultural credit by identifying the most important economic and social characteristics affecting the demand for agricultural loans. Farmers need agricultural credit as a source of financing due to their weak financial capabilities، and that farmers’ lack of access to credit may negatively affect the achievement of the level of production that maximizes profit or allow farmers to apply and use modern technologies or develop existing agricultural projects. Cross-sectional data were collected for a random sample of (275) farmers in Baghdad governorate. The Logit model was used to determine the most important factors affecting agricultural loans، which include gender، age، educational level، farm size، experience، and type of tenure، in addition to statistical description and correlation analysis، using The statistical program (EViews10), The results showed that years of experience، farm size، gender، and age have a positive and significant effect، while the educational level has a negative and significant impact، as the higher the educational level of farmers، the greater their ability to obtain employment outside the agricultural sector، such as business in government jobs. or trade and others، while the impact of the type of tenure was weak، and thus the research recommends the need to develop a credit policy that takes into account the studied characteristics of farmers and enhance their capabilities through guidance and training in addition to supporting women farmers .